2006
DOI: 10.1016/j.jpainsymman.2006.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Microbiological and Physicochemical Stability of Fentanyl and Sufentanil Solutions for Patient-Controlled Delivery Systems

Abstract: The aim of this study was to assess the microbiological and physicochemical stability of opioid solutions containing fentanyl or sufentanil and thereby determine the feasibility of extending the expiration dates after mixing. Five systems containing fentanyl or sufentanil solutions at 50 microg/mL in portable patient-controlled analgesia (PCA) systems were filled and stored at room temperature for 14 days. They were sampled immediately after preparation, at day 3, and each day of the following weeks. Microbiol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 24 publications
0
5
0
1
Order By: Relevance
“…Moreover, fentanyl is stable when mixed with midazolam and either hyoscine butyl bromide or metoclopramide and stored in polypropylene syringes for 1 week at ≤ 32°C (Peterson et al 1998). Solutions of fentanyl diluted with 0.9% saline are stable when stored in a polyvinyl chloride portable infusion pump for 14 or 30 days at 23°C (Chapalain-Pargade et al 2006). Oxycodone, either pure or diluted with 0.9% saline, 5% dextrose, or water for injection, is stable when stored at room temperature for 28 days in a PCA device (Amri et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, fentanyl is stable when mixed with midazolam and either hyoscine butyl bromide or metoclopramide and stored in polypropylene syringes for 1 week at ≤ 32°C (Peterson et al 1998). Solutions of fentanyl diluted with 0.9% saline are stable when stored in a polyvinyl chloride portable infusion pump for 14 or 30 days at 23°C (Chapalain-Pargade et al 2006). Oxycodone, either pure or diluted with 0.9% saline, 5% dextrose, or water for injection, is stable when stored at room temperature for 28 days in a PCA device (Amri et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that fentanyl sterile solution packaged in medical and hospital devices, such as polypropylene syringes, polyvinylchloride bags and patient-controlled delivery systems requires especial precautions for maintaining drug stability, depending on the packaging material, temperature, storage life and duration of drug administration (DONNELLY, 2005; CHAPALAIN-PARGADE et al, 2006;MCCLUSKEY et al, 2009). …”
Section: Resultsmentioning
confidence: 99%
“…10,11 Currently, mixtures of FC and NH are often not commercially available; therefore, pharmacists in community or hospital pharmacy practices can provide these mixed liquors by blending the respective components in a 0.9% sodium chloride injection solution and storing the ready-to-use solution for PCA. 12,13 However, to our knowledge, the stability of FC and NH in a 0.9% sodium chloride injection solution has not yet been reported. Therefore, the objective of the current study was to investigate the physical compatibility and chemical stability of the binary admixture of FC and NH prepared with a 0.9% sodium chloride injection solution and stored at temperatures of 4°C and 25°C in polyvinyl chloride (PVC) bags and glass bottles for up to 72 h and provide a theoretical basis for clinicians to guide the safe and rational use of these drugs in PCA.…”
Section: Introductionmentioning
confidence: 94%
“…The FC, NH and mixtures of FC and NH in the injectable sodium chloride solutions were degraded by heating at 60°C for 5 h under the following conditions: 0.1 mol/L hydrochloric acid (HCl), 0.1 mol/L sodium hydroxide (NaOH), and 3% hydrogen peroxide (H 2 O 2 ). 8,12 After completing the degradation preparations, the solutions were assessed by HPLC assay.…”
Section: Stability Indicationmentioning
confidence: 99%